Numerical Investigation on the Flow Field of Muzzle Decompression Device for the Barrel Recoil Gun - Zilong Liu; Jinsong Dai; Shengye Lin; Dong Zhou; Maosen Wang; Haifeng Wang (Shock and Vibration)
A structured dynamic overlapping grid and a user-defined function are used to study the projectile launching process, and the hybrid Roe scheme is used to solve the flow field with strong shock wave. The launching process of a projectile with a muzzle decompression device is numerically simulated by using a three-dimensional transient model, and the flow field inside the muzzle decompression device and the development process of the muzzle flow field in the projectile launching process are discussed in detail. Compared with no device, the muzzle decompression device can effectively reduce the peak pressure around the muzzle; the numerical results are in agreement with the corresponding experimental values. The numerical investigation in this paper is helpful to understand the mechanism of pressure reduction of the device. It also provides a new way to reduce the muzzle pressure of aircraft gun.